(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Unification theory with no extra dimensions, using a vacuum structure and opposite from fields based. The first part deals with the unification of the strong nuclear force and the gravitational force. Strong nuclear force, with an attraction of 10.000 Newtons is which makes space to curve generating acceleration, more matter, more acceleration. Gravitational force is moved to work with more than 30 decimals. The second part describes the hypothetical structure for the quantum vacuum to be able to work as a superconductor of matter as well as of smaller subatomic particles (like photons or neutrinos) inside a 3 states multistable system that allows fundamental particles motion as described in the Standard Model.